Lo pronombres él y ello marcando la dificultad de aprendizaje de los alumnos de Español en el aula del 3º año g de la E. E. E. F. M São Francisco Xavier: una propuesta didáctica - SILVA, Joelson Silva da (2019)
In the learning of Spanish by Brazilian students there are certain linguistic errors resulting from the similarity between the two languages. Among so many, there’s the wrong use of pronouns él and ello. Through an investigation with the students of the third year of a public school, this study verifies such occurrence and applies a didactic activity to heal it. But first, a review is made of the main theoretical propositions of learning a foreign language, where the models of Contrasting Analysis (AC), Error Analysis (AE) and Interlingual (IL) are found. In this way, are analyzed the writings of Santos Gargallo (1993), Andrade (2002), Baralo (2004), Durão and Schardosim (2011), among others, fundamental to understand the causes of the misunderstandings and to propose effective means to correct them.